The rethinking and enhancement of the natural and cultural heritage of the cultural landscapes: the case of Secovlje and Janubio saltpans - Luis Gregorio Abad Espinoza (PASOS Revista de Turismo y Patrimonio Cultural, 2019)
Cultural landscapes represent a complex category where the nature-culture dichotomy seem to not be able to unfold the main features and the profound relations that humans have with the environment. Drawing on ethnographic data collected in the saltpans of Secovlje (Slovene Istria) and Janubio (Lanzarote-Canary Islands) this article examines informant`s perceptions about the awareness of the importance and the enhancement of the holistic values of both saltpans, as well as the impacts and benefits of tourism. Comparing these perceptions about both cultural landscapes, I try to suggest that the complex fruitfully relations between humans and nature in these saltpans are at odds with the neoliberal logic of nature which exploit and commoditize its resources depriving them of their respective agency. A sustainability to contrast the harmful activities of the market ought to be understood not as a simply isolation and fencing of nature for the sake of conservation, but as a preservation that need to foster the continuity of the deep interactions between human culture and non-human nature which are the core of the cultural landscapes.